Neuro-fuzzy control of a robotic manipulator - Gierlak, Piotr; Muszyńska, Magdalena; Żylski, Wiesław (1938-2018) (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, to solve the problem of control of a robotic manipulator?s movement with holonomical constraints, an intelligent control system was used. This system is understood as a hybrid controller, being a combination of fuzzy logic and an artificial neural network. The purpose of the neuro-fuzzy system is the approximation of the nonlinearity of the robotic manipulator?s dynamic to generate a compensatory control. The control system is designed in such a way as to permit modification of its properties under different operating conditions of the two-link manipulator.
Keywords: robotic manipulator; force control; neuro-fuzzy systems